Advanced AI Techniques for Retail Supply Chain Sustainability: Models, Applications, and Real-World Case Studies (Journal of Science & Technology, 2020)
The imperative to achieve environmental sustainability is increasingly influencing the strategic direction of supply chain management, particularly within the complex and dynamic retail sector. This research endeavors to illuminate the potential of advanced artificial intelligence (AI) technologies to catalyze sustainable practices throughout the intricate network of retail supply chains. By meticulously examining a confluence of AI models, applications, and real-world case studies, this investigation seeks to elucidate the practical implications of AI in optimizing resource allocation, minimizing environmental externalities, and fostering social responsibility.The study commences with a rigorous exploration of the theoretical underpinnings of AI, encompassing a diverse array of techniques such as machine learning, deep learning, and natural language processing, as applied to the multifaceted domain of supply chain management. A granular taxonomy of AI-driven models is developed, encompassing critical areas such as demand forecasting, inventory optimization, transportation and logistics management, supply chain risk assessment, and reverse logistics. The efficacy of these models in addressing the complex challenges of sustainability is rigorously evaluated, with a particular emphasis on their capacity to reduce carbon emissions, minimize waste generation, conserve water resources, and promote circular economy principles.Furthermore, the research delves into a comprehensive analysis of AI applications within the context of retail supply chains, encompassing sustainable sourcing practices, circular economy initiatives, and the promotion of ethical labor conditions. Specific focus areas include the utilization of AI for supplier selection, traceability, and risk mitigation; the development of AI-driven systems for product lifecycle management and end-of-life management; and the application of AI to optimize transportation and distribution networks for reduced environmental impact. Through in-depth case studies of leading retail organizations, the practical implementation of AI-powered solutions is scrutinized, with a focus on quantifiable sustainability metrics and performance indicators. The investigation also explores the synergistic relationship between AI and emerging technologies such as blockchain, the Internet of Things, and digital twins in creating resilient and eco-friendly supply chain ecosystems.This research offers a comprehensive exploration of AI's role in sustainable retail supply chains, extending beyond previous studies by delving deeper into the intricacies of model development, application, and real-world implementation. The investigation incorporates a rigorous methodology, combining theoretical frameworks with empirical evidence and industry insights to provide a holistic understanding of the subject matter. By examining a diverse range of AI techniques and their applications across various supply chain functions, this research contributes to the advancement of knowledge in the field and offers valuable insights for practitioners, policymakers, and researchers seeking to drive sustainable transformation within the retail industry.The findings of this research are expected to provide actionable recommendations for retailers, policymakers, and researchers seeking to harness the transformative power of AI to mitigate environmental and social impacts while achieving long-term business objectives. Moreover, the research underscores the critical role of AI in enabling data-driven decision-making, optimizing resource utilization, and fostering innovation throughout the retail supply chain, ultimately contributing to a more sustainable and resilient global economy.To achieve this, the research will employ a mixed-methods approach, combining quantitative and qualitative research methodologies. Quantitative analysis will be utilized to assess the performance of AI models in predicting demand, optimizing inventory levels, and reducing transportation emissions. Qualitative research, including case studies and interviews with industry experts, will provide insights into the challenges and opportunities associated with AI implementation in retail supply chains. Additionally, the research will employ a comparative analysis of different AI techniques and their impact on various sustainability metrics to identify the most effective approaches for different supply chain contexts.By adopting a multidisciplinary perspective, this research aims to bridge the gap between theoretical advancements in AI and their practical application in the retail industry. The findings of this study are expected to contribute to the development of innovative AI-driven solutions for sustainable supply chain management, ultimately leading to a more environmentally responsible and socially equitable retail sector.